Error management in new product development teams - Akgun, Ali E.; Keskin, Halit; Golgeci, Ismail; Ozerden, Selin S. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
A few studies have examined error management culture (EMC) in the new product development (NPD) team context. This study investigates the role of EMC on the process outcomes (e.g. team learning (TL) and team creativity (TC)) and project performance (e.g. new product financial performance-NPFP) of NPD projects within the boundary condition of projects' task complexities (e.g. routines and existing knowledge of tasks). By studying 179 NPD projects, we found that error recognition, psychological safety, and team reward attitude (TRA) create an effective EMC for NPD teams. We also revealed that effective EMC positively impacts TL and TC, and NPFP. Finally, we showed that the routine aspect of task complexity moderates the relationship between EMC and TL. In contrast, the existing knowledge aspect of task complexity does not moderate the relationships between EMC and process and project outcomes.
Keywords: Error management culture; new product development; team learning; team creativity; project performance; task complexity; PSYCHOLOGICAL SAFETY; CULTURE; IMPACT; PERFORMANCE; LEADERSHIP; ATTITUDE; Business & Economics; Science & Technology - Other Topics